Effect of a High Protein Weight Loss Diet on Weight, High-Sensitivity C-Reactive Protein, and Cardiovascular Risk among Overweight and Obese Women: A Parallel Clinical Trial. (6th August 2013) - Azadbakht, Leila; Izadi, Vajihe; Surkan, Pamela J.; Esmaillzadeh, Ahmad
Abstract : Studies regarding the effects of high protein (HP) diets on cardiovascular (CVD) risk factors have reported contradictory results. We aimed to determine the effects of an HP diet on CVD risk factors and high-sensitivity C-reactive protein (hs-CRP) among overweight and obese women. In this randomized controlled trial, we recruited 60 overweight and obese women, aged 20–65, into an HP or energy-restricted control diet for three months (protein, carbohydrate, and fat: 25%, 45%, and 30% versus 15%, 55%, and 30%, resp.). Total protein was divided between animal and plant sources in a 1 : 1 ratio, and animal sources were distributed equally between meats and dairy products. Fasting blood samples, hs-CRP, lipid profile, systolic and diastolic blood pressure, and anthropometric measurements were assessed using standard guidelines. Percent change was significantly different between the two diet groups for weight (standard protein (SP): −3.90 ± 0.26 versus HP: −6.10 ± 0.34%; P < 0.0001, resp.) and waist circumference (SP: −3.03 ± 0.21 versus HP: −5.06 ± 0.28%; P < 0.0001, resp.). Percent change of fasting blood glucose (FBG) substantially decreased in the control group compared to the HP group (−9.13 ± 0.67 versus −4.93 ± 1.4%; P = 0.01, resp.). Total cholesterol, systolic blood pressure (SBP), and diastolic blood pressure (DBP) decreased both in the HP and in the control diet groups ( P = 0.06, P = 0.07, and P = 0.09, resp.); however, the results were marginally significant. Serum levels of hs-CRP were reduced both in the control (−0.08 ± 0.11%, P = 0.06) and in the high protein groups (−0.04 ± 0.09%, P = 0.06). The energy-restricted HP diet resulted in more beneficial effects on weight loss and reduction of waist circumference. CVD risk factors may improve with HP diets among overweight and obese women. When using isoenergetic weight loss diets, total cholesterol, hs-CRP, and SBP were marginally significantly reduced, independent of dietary protein content. This trial is registered with ClinicalTrials.gov NCT01763528 .